2007
DOI: 10.1155/2007/34763
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous Endometritis: A Challenging Imitator of Endometrial Carcinoma

Abstract: Xanthogranulomatous inflammation is a distinguished histopathological entity affecting several organs, predominantly the kidney and gallbladder. So far, only a small number of cases of xanthogranulomatous inflammation occurring in female genital tract have been described, most frequently affecting the endometrium and histologically characterized by replacement of endometrium by xanthogranulomatous inflammation composed of abundant foamy histiocytes, siderophages, giant cells, fibrosis, calcification and accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 4 publications
2
35
1
Order By: Relevance
“…In 2007 Dogan-Ekici and Usubutun et al [2] reported 1 case of XGE mimicking endometrial carcinoma, as in the present case, which was mimicking cervical carcinoma both clinically and radiologically.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In 2007 Dogan-Ekici and Usubutun et al [2] reported 1 case of XGE mimicking endometrial carcinoma, as in the present case, which was mimicking cervical carcinoma both clinically and radiologically.…”
Section: Discussionsupporting
confidence: 56%
“…Our case also showed positivity for a microorganism (gram-positive cocci). However, Buckley et al [7] and Dogan et al [2] found no microorganism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xanthogranulomatous endometritis (XGE) macroscopically mimics endometrial carcinoma, as it converts endometrium into friable yellowish tissue 1 . XGE is described in association with endometrial carcinoma 2,3,4 .…”
Section: Xanthogranulomatous Endometritis Coexisting With Carcinoma Cmentioning
confidence: 99%